2003
DOI: 10.1172/jci200316432
|View full text |Cite
|
Sign up to set email alerts
|

CD28-dependent Rac1 activation is the molecular target of azathioprine in primary human CD4+ T lymphocytes

Abstract: Azathioprine and its metabolite 6-mercaptopurine (6-MP) are immunosuppressive drugs that are used in organ transplantation and autoimmune and chronic inflammatory diseases such as Crohn disease. However, their molecular mechanism of action is unknown. In the present study, we have identified a unique and unexpected role for azathioprine and its metabolites in the control of T cell apoptosis by modulation of Rac1 activation upon CD28 costimulation. We found that azathioprine and its metabolites induced apoptosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
336
1
7

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 291 publications
(357 citation statements)
references
References 49 publications
13
336
1
7
Order By: Relevance
“…Classic immunosup pressive drugs for IBD therapy include azathioprine or 6 mercaptopurine [10][11][12][13][14] , methotrexate 15 and ciclosporin A or tacrolimus 16 . The latter drugs have been used in stud ies for induction of remission in patients with ulcer ative colitis, methotrexate has been used for induction and maintenance of remission in Crohn's disease and azathio prine is frequently used for mainten ance of remission in both Crohn's disease and ulcerative coli tis 14,15,17 .…”
Section: Classic Immunosuppressive Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…Classic immunosup pressive drugs for IBD therapy include azathioprine or 6 mercaptopurine [10][11][12][13][14] , methotrexate 15 and ciclosporin A or tacrolimus 16 . The latter drugs have been used in stud ies for induction of remission in patients with ulcer ative colitis, methotrexate has been used for induction and maintenance of remission in Crohn's disease and azathio prine is frequently used for mainten ance of remission in both Crohn's disease and ulcerative coli tis 14,15,17 .…”
Section: Classic Immunosuppressive Drugsmentioning
confidence: 99%
“…Thus, RAC1 activation is suppressed, leading to inhibited activation of cells in both the innate and adaptive immune systems. In T cells for instance, azathioprine and 6 mercaptopurine can cause apoptosis through RAC1 inhibition 10 . Furthermore, T cell apopto sis has been shown to correlate with responsiveness to azathioprine or 6 mercaptopurine in patients with IBD 10 .…”
Section: Classic Immunosuppressive Drugsmentioning
confidence: 99%
“…Consistent with our results, Thr142 residue of nerve growth factor (NGF)I-B was identified as a substrate for ERK2 in vivo and Ser105 was also shown to be phosphorylated by MAPK pathway when stimulated by NGF (Slagsvold et al, 2002). Activation of MAPK signaling pathway by 6-MP seems to be unique for the Nur77-induced stabilization of HIF-1a, because 6-MP suppresses mitogen-induced extracellular kinase (MEK) phosphorylation when it leads to the mitochondrial apoptotic pathway in primary human CD4 þ T lymphocytes (Tiede et al, 2003). MEKK1 also suppresses the mitogenic effect of Nur77 that is induced by the epidermal growth factor and serum, by inhibiting its DNA binding and transactivation function in lung cancer cell lines (Kolluri et al, 2003).…”
Section: -Mp Increases the Capillary-tube Formation Of Human Umbilicmentioning
confidence: 99%
“…This reaction is regulated through GTPase-activating proteins. It has been shown that 6-MP and its metabolite 6-T-GTP can target Rac1 in CD4 + T cells, blocking T cell activation (10). Interestingly, 6-T-GTP also can bind other small Rho-GTPases such as Cdc42, RhoA, and Rac2, yet, it can only block the activity of Rac1 and Rac2 (11).…”
mentioning
confidence: 99%